What Regulatory Frameworks are More Conducive to Mobile Banking? Empirical Evidence from Findex Data - Gutierrez, Eva; Singh, Sandeep (World Bank, Washington, DC, 2014)
Mobile banking services offer great potential to expand financial services, particularly payment services, to the poor. They also provide a convenient and cost effective way to access bank accounts. This paper constitutes a first attempt to explain statistically what factors contribute to mobile banking usage, with a particular focus on the regulatory framework. The authors construct an index that measures the existence of laws and regulation that support mobile banking activity for 35 countries. Using variations in regulatory environments across these countries and armed with newly released data on mobile banking usage by approximately 37,000 individuals in these 35 countries, the paper sheds light on the importance of laws and regulation in supporting mobile banking. The analysis finds that a supporting regulatory framework is associated with higher usage of mobile banking for the general population as well as for the unbanked.